Implementasi Kebijakan Tetangga Baik (Good Neighbor Policy) China Pada Masa Presiden Hu Jintao di Greater Mekong Sub-Region (GMS) - Nurjannah Abdullah (Department of International Relations, Hasanuddin University, 2021)
This research was conducted to understand the implementation of models and factors that influence China's Good Neighbor Policy decision making during the reign of Hu Jintao in the Greater Mekong Sub-Region. By using an Adaptive decision-making model, this paper tries to describe the internal and external factors that influenced President Hu Jintao to choose a model of revitalization of cooperation and infrastructure development as well as economic corridors as a manifestation of the implementation of the Good Neighbors policy in GMS. This study used a qualitative approach and used secondary data as the source of the analyzed data. Penelitian ini dimaksudkan untuk memahami model implementasi dan faktor yang mempengaruhi pengambilan keputusan pelaksanaan kebijakan Tetangga baik (Good Neighbour Policy) China Pada Masa pemerintahan Hu Jintao di Greater Mekong Sub Region. Dengan menggunakan model pemgambilan keputusan Adaptif, tulisan ini mencoba mendeskripsikan faktor internal dan ekternal yang mempengaruhi Presiden Hu Jintao memilih model revitalisasi kerjasama dan pembangunan infrastruktur serta koridor ekonomi sebagai wujud implementasi kebijakan Tetangga yang Baik di GMS. Penelitian ini menggunakan pendekatan kualitatif dan menggunakan data sekunder sebagai sumber data yang dianalisis.